Trabectedin plus Pegylated Liposomal Doxorubicin: Retrospective Analysis in Heavily Pretreated Platinum-sensitive Ovarian Cancer. Issue 5 (September 2015) - Nicoletto, Maria Ornella; Baldoni, Alessandra; Casarin, Alessandra; Randon, Giovanni; Nardin, Margherita; Baretta, Zora; Lardelli, Pilar; Nieto, Antonio; Alfaro, Vicente; Rigamonti, Claudia; Conte, Pier Franco
Purpose: This retrospective analysis evaluated treatment with trabectedin plus pegylated liposomal doxorubicin (PLD) in 34 heavily pretreated patients (median number of previous lines, 3; range, 2-10) with platinum-sensitive relapsed ovarian cancer (ROC) at a single center in Italy. Methods: Trabectedin/PLD treatment consisted of trabectedin administered every 3 weeks as a 3-hour intravenous (i.v.) infusion at a dose of 1.1 mg/m 2, immediately after PLD 30 mg/m 2 i.v. infusion. Study objectives were the evaluation of the objective response rate (ORR), progression-free survival (PFS) and overall survival (OS). Results: Three complete responses and 8 partial responses were observed, with an ORR of 32.4% (95% CI, 17.450.5%). Median PFS was 6.1 months (95% CI, 4.4-8.9 months). Median OS was 16.3 months (95% CI, 6.8-23.5). Most responses (9 of 11) were found in patients with partially platinum-sensitive disease (ORR 40.9% in this subset; median PFS 6.8 months and median OS 20.8 months). Grade 3 treatment-related adverse events consisted of nausea/vomiting (n = 5; 14.7%), mucositis (n = 2; 5.9%), alanine aminotransferase increase, anemia and neutropenia (n = 1 each; 2.9%). Conclusions: The overall findings appear consistent with those previously observed in a randomized controlled clinical trial, and support the use of trabectedin/PLD in heavily pretreated patients with platinum-sensitive ROC, especially those with partially platinum-sensitive disease.